Light‐Responsive Helical Polypeptides Capable of Reducing Toxicity and Unpacking DNA: Toward Nonviral Gene Delivery1. Issue 35 (5th July 2013) - Yin, Lichen; Tang, Haoyu; Kim, Kyung Hoon; Zheng, Nan; Song, Ziyuan; Gabrielson, Nathan P.; Lu, Hua; Cheng, Jianjun
<x xml:space="preserve">Abstract</x> Gene delivery vehicles: Helical, cationic polypeptides with light‐responsive domains showed potent membrane activity and promoted efficient cellular internalization of DNA (see picture). After transfection, a light trigger induces protecting‐group removal to expose anionic carboxylate groups. The reduced cationic charge and helix distortion of the polypeptides result in enhanced DNA unpacking and reduced material toxicity because of the eliminated membrane activity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>